School-Community-Business Collaboration Model for Strengthening Islamic Religious Education - Muhammad Maftuhin; Muhammad Ardiyanto; Siti Marwiyah; Dwi Noviatul Zahara; M. Makhrus Ali (LP2M INSURI Ponorogo, 2025)
Islamic Religious Education (IRE) plays a strategic role not only in transmitting religious knowledge but also in strengthening character, moral values, and socio-economic awareness. However, its implementation often faces challenges, particularly the limited collaboration between schools, communities, and the business sector, which reduces its broader social impact. This community service study aims to develop a collaborative school–community–business model to strengthen IRE implementation and to evaluate its impact on participants’ understanding and commitment to integrated religious, social, and economic development. The program applied a participatory and collaborative approach involving IRE teachers, students, community leaders, and business representatives. Activities were conducted over three months in school and community settings through several stages, including needs assessment, discussion forums, capacity-building training, program implementation, and evaluation. The collaborative initiatives included religious and social activities, mosque- and school-based Islamic economic empowerment programs, and educational facility support from business partners. The results show a significant improvement in IRE implementation. Evaluation data indicate that 76% of IRE teachers reported increased confidence and competence in applying socially integrated IRE, while 71% of students demonstrated improved understanding of the relationship between religious teachings and socio-economic practices. In addition, four collaborative programs were successfully established, including a productive zakat initiative, a school-based Islamic cooperative, joint religious–social activities, and business-supported educational facilities. These findings demonstrate that the collaborative model effectively strengthens IRE as an integrative and sustainable framework for community-based Islamic education.